Capital structure and profitability in a tax-free country: evidence from the UAE - Tebourbi, Imen; Irene, Wei Kiong Ting; Qian, Long Kweh; Al Huseini, Harith Ali Hamood (Inderscience Enterprises Ltd., 2020)
The balance between debt and equity is a key factor explaining profitability. This study examines how capital structure affects the profitability of firms listed on stock exchanges in the United Arab Emirates (UAE), a country that does not have a federal corporate income tax regime. The proxies of capital structure used include total, short-term, and long-term debt ratios, while those of profitability are return on assets and return on equity. Over a 2001-2016 sample period, this study documents a significantly negative association between capital structure and profitability. This study finds that the negative association is mainly found in companies with a high level of debts. The results of this study not only imply that information asymmetry exists, they also highlight how capital structure and profitability are associated in the context of a corporate tax-free country.